Business planning : a guide to business start-up - Butler, David (Butterworth-Heinemann, 2000)
A readable and structured guide for the increasing numbers of people each year who consider setting up a small business or becoming self-employed. 'Business Planning' outlines the options and risks involved in setting up a business. The importance of thorough planning is often overlooked and only becomes evident if the business fails. This is highlighted in a recent study by the SFEDI of 486 bankers and accountants where lack of planning was the most common reason cited as to why businesses fail. 'Business Planning' shows how to avoid this failure by focusing on the planning stage and building.- Resumé vydavatel
Keywords: podniky; podnikatelské projekty; business enterprises; business planning; elektronické knihy; příručky; electronic books; handbooks and manuals